Propuesta de iluminación aplicando nuevas tecnologías para el sendero ecológico sur-norte de la ciudad de Loja. - Alvarado Arias, Camilo José (2017)
Work of awarding of title accomplishes an analysis for public ornamental illumination for the ecological southern path and north of Loja's city itself in the present, the fact that you have an extension brought near of 14,24 km, with the executed study determined him all variables the fact that you integrate a system of illumination, the calculation developed considering the methodology proposed in the ARCONEL's regulation, the INEN 069 and technical documentation related with the theme, taking place to determine levels of illumination and uniformity necessary according to like establishes it the regulations in force of the country. For this work considered him two designing proposals, which are, conventional (buried net), conformed illumination with technology of illumination of Sodio of Loud pressure and the unconventional illumination (photovoltaic), shaped with technology of illumination LED, considering the technical ground rules of constructions established by the MEER for the design the electric design for the system of illumination. The design and sizing for the conventional system will have 10 kVA's 18 single-phase transformers, this proposal implicates approximately 7,23 driver's km of isolated copper XLPE #2 AWG for half a tension, 16,4 driver's km of isolated copper type TTU # 6 AWG for public illumination, 15 aerial transitions – subterranean, 393 wells type To, 126 wells type B, 33 wells type C, settings ashore, components of section and protection and 499 ornamental poles with his respective light of sodium, finally the total investment comes from USD $ 1,4 millioN. The design and sizing for the unconventional system you will tell with 499 panels monocristalicos of 300W, 499 acid lead batteries of 200 Ah, 499 investors of 200W, 499 charging 30 regulators To, 2,5 driver's km #12 AWG and 499 ornamental poles with his respective light LED, finally the total investment of this proposal comes from USD $ 1,2 million. The utilization of the software DiaLUX® allowed constructing a radiant map of the place of study, in this the exact position out of every light, false colors can be visualized, and his uniformity having like value of uniformity of 0,41 for the proposal of illumination LED and 0,389 for the proposal of illumination of sodium of loud pressure, you developed the technical cost-reducing analysis for the two proposals.